Analisis Keterampilan Berpikir Kritis Peserta Didik Kelas XII SMAN 1 V Koto Kampung Dalam Tentang Materi Pembelahan Sel - Fitrah Herninda; S. Syamsurizal (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
One of the 21st Century skills that must be possessed by students is critical thinking skills. Critical thinking can make students able to develop ideas, formulate and solve problems in making decisions. The purpose of this study was to determine the level of critical thinking skills of students on cell division material at SMAN 1 V Koto Kampung Dalam. This type of research is descriptive quantitative research. The sample in this study was 30 students of class XII MIPA SMAN 1 V Koto Kampung Dalam which consisted of four classes. The sampling technique used is simple random sampling. The instrument used is a question sheet in the form of a valid description (essay). Data analysis technique using Microsoft Excel. Based on the results of the study, it is known that the critical thinking skills of class XII students are still in very low qualifications with an average of 40.42%. The existence of these results is expected to provide information about critical thinking skills so that teachers can apply appropriate learning strategies and models in developing students' critical thinking skills.